Os pressupostos crítico-transcendentais da liberdade em Kant - Nascimento, Julia Stephanie Abrão Seidl do (2021)
The present dissertation aims to present the critical transcendental assumptions of freedom in the Critique of Pure Reason and in the Groundwork of the Metaphysic of Morals. The research first investigates how it is possible to conceive metaphysics and to place it in the safe scope of science. The faculties which enable knowledge will thus be presented: the lower faculty refers to the sensitivity, which is comprehended as a receptive faculty, whilst the higher faculties comprehend the understanding, judgment and reason. When it comes to the understanding, its pure forms will be demonstrated, which are the categories that give shape to the experience, where the metaphysical and transcendental deductions demonstrate their possibility. The faculty of judgment will properly provide the discussion expressed in the Second Analogy of The Experience, which makes it possible to establish causality within the legitimate scope of experience. With the delimitation of causality in the sensitive field, and its legitimacy, the first chapter’s discussion ends. The second chapter is dedicated to dealing with the reason stricto sensu, whose syllogistic faculty is presented, along with its path to the ideas of reason, which extract an object conceived as absolute, theme of the rational cosmology. In this context emerge the antinomies of pure reason, where the discussion will be delimited to the third antinomy, which demonstrates a possible conflict between two argumentative lines: the first defends a causality by freedom, whilst the second denies causality by freedom, conceiving as possible only a causality by nature. The conflict’s solution is given by Kant when he presents a legitimate regulatory use for the ideas of reason. Thence we will discuss about the Kantian practical philosophy, which consists of finding an a priori principle, derived from pure reason. The moral acting is called duty and it ought to align itself with the moral law not only externally, but also internally, and it takes place out of respect for the moral law. In an ascertainment process, the categorical imperative makes it possible to test an action, by demonstrating its ethical principle. The will’s autonomy demonstrates the capacity of a rational being to legislate for oneself, at the same time that we follow this law, which is universally valid, and rational beings are endowed with it. Its possibility demonstrates our capacity of being free, which differentiates us from other beings that act only according to laws and not according to their representations, conciliating our possibility of being free with the obedience to the moral law.